The role of referral hiring on immigrant labor market outcomes - Lee, Marcos Ki Hyung (2017)
The aim of this dissertation is to investigate whether referral hiring leads to better job search and labor market outcomes for immigrants in São Paulo. To do so, we use a proxy for referral hiring, the share of same nationality workers in a firm one year before hiring, and estimate wage and turnover regression with a matched employer-employee dataset (RAIS). We find that referral hiring lower immigrant\'s wages at hiring, that is, if the proposed proxy increased by 10 p.p., wages would decrease by 1.9%. We also devise a couple of placebo test that reinforce the results we have found. We identify that nationalities with low education workers absorb all the negative impact. Other possible channels could be the size of immigrant networks and immigration age of nationalities, but we find no impact, although these exercises have several identification problems. Future steps include developing a theoretical framework that can rationalize the results.